Validation and results of a novel survey assessing decisional balance for a whole food plant-based diet among US adults - Jovanovic, Christine E. S.; Kalam, Faiza; Granata, Frank; Pfammatter, Angela F.; Spring, Bonnie (Frontiers in Nutrition, 2022)
Importance: Consuming a whole food plant-based diet (WFPBD) is a promising, low-risk strategy for reducing risk of prevalent chronic disease and certain cancers, with synergistic benefits for climate and environment. However, few US adults report consuming a WFPBD. Understanding the reasons for this inconsistency is important for developing and implementing interventions for promoting a WFPBD. However, no research to elucidate decisional balance driving current consumption patterns in the US exists. Objective: This research aims to validate an online survey to assess decisional balance for the consumption of a WFPBD, describe attitudes and beliefs towards adopting a WFPBD, and evaluate socio-demographic differences in decisional balance for consuming a WFPBD among a convenience sample of US adults. Design: Online cross-sectional data collection followed by confirmatory factor analysis (CFA), validation of internal consistency, and examination of invariance across socio-demographic variables. Sensitivity analysis of full versus truncated survey to predict self-reported dietary patterns and consumption behaviors were evaluated. Results of the survey and significant differences by socio-demographics were assessed. Setting: Online survey based on previous research, created via Qualtrics and administered through MTurk. Participants: 412 US adults, majority female (66%), White (75%), 30 to 60 years old (54%), ≥ Bachelor’s degree (85%), and earning ≥ $45K (68%). Main Outcomes and Measures: Factor loadings, covariance of survey items, associations with self-reported dietary pattern and consumption measures, and differences in pros, cons, and decisional balance across socio-demographic variables. Results: CFA reduced the survey from 49 to 12 items and demonstrated invariance across socio-demographic variables. Pros and cons varied inversely and significantly (cov= -0.59), as expected. Cronbach’s α’s for subscales in the final, reduced model were high (>0.80). Pros, cons, and decisional balance in both the full and the reduced model were significantly (p<0.05) associated with self-reported dietary pattern and consumption. Conclusions and Relevance: Our analyses indicate the WFPBD Survey is a parsimonious and psychometrically sound instrument for evaluation of decisional balance to consume a WFPBD diet among our sample of US adults. These results may be instrumental for development and deployment of interventions intended to promote consumption of a WFPBD in the US.